An unusual presentation of huge paraovarian cyst as papillary serous cyst adenofibroma: a rare case report - Agrawal, Namita; Gupta, Nishi; Chandra, Sukriti; Gupta, Shubha; Fayyaz, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Paraovarian cysts constitute 10-20% of all adnexal masses and are usually less than two centimeter in diameter. Authors reported a 20-year-old unmarried female with vague abdominal discomfort since 1 year. On examination abdomen was uniformly distended with central position of umbilicus. Ultrasonography showed a large cystic mass extending from pelvis to pancreas likely of ovarian origin. Biochemical evaluation was not suggestive of malignant nature of this cystic mass. So, with due care of cosmesis, surgery was planned. After the midline vertical incision, peritoneal washings were collected for oicytological analysis to further exclude malignancy. Then 5mm cannula with trocar was inserted into the cyst to suck out the fluid then shrunken cystic wall was exteriorised. Right ovary was absolutely healthy. Enucleation of the cyst was done with preservation of ovary. Histopathology reported as a papillary serous cyst adenofibroma. Follow up period was uneventful.